Determination of pre-harvest interval for fenvalerate and acephate in tomato and yard long bean using Gas Chromatography - Ahmed, Md Sultan; Prodhan, Mohammad Dalower Hossain; Begum, Afroza; Afroze, Marina; Dutta, Nirmal Kumar; Emtia, Chandrima; Sarker, Debasish (Asian-Australasian Journal of Food Safety and Security, 2022)
The study was carried out to detect and quantify the left over residue of fenvalerate and acephate in tomato and yard long bean using Gas Chromatography coupled with Flame Thermionic Detector. Four supervised field trials were undertaken sprayed with the prescribed dose of fenvalerate at the rate of 1mL/L of water and acephate at the rate of 2g/L of water. The samples of tomato and yard long bean were collected at 0, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14 and 15 days after spray (DAS). The residue of acephate was detected up to 11 DAS in tomato and 14 DAS in yard long bean and all of the detected quantities were above Maximum Residue Limit (MRL) set by European Union. No residue was detected at 12 DAS in tomato and 15 DAS in yard long bean. The residue of fenvalerate was detected up to 12 DAS in tomato and 13 DAS in yard long bean, of which the quantities of residue of fenvalerate was above EU-MRL at 9 DAS in tomato and 11 DAS in yard long bean. Fenvalerate contained 0.076-0.008 mg/kg residue in tomato and 0.049-0.021 mg/kg residue in yard long bean which were below EU-MRL at 10 to 12 DAS in tomato and 12 to 13 in yard long bean which were below EU-MRL. No residue was detected at 13 DAS in tomato and 14 DAS in yard long bean. So, in case of acephate the pre-harvest interval (PHI) was determined at 12 DAS in tomato and 15 DAS in yard long bean and for fenvalerate it was 10 DAS in tomato and 12 DAS in yard long bean. Asian Australas. J. Food Saf. Secur. 2022, 6 (2), 73-80